Pelatihan Penggunaan Virtual Chemistry Laboratory dalam Pembelajaran Bagi Calon Guru Kimia - Amsad, Lusia Narsia; Jukwati; Deminggus, Frans (J-Abdimas Cenderawasih, 2024)
The training is descriptive research that describes the results of implementing the Virtual Chemistry Lab for all prospective chemistry teachers, as well as general science skills. The research subjects for this topic are second and third year chemistry students who have completed basic chemistry courses. This activity lasted for two days and began with the introduction stage of the Chemcollective Virtual Chemistry Lab software, then continued with the implementation stage, especially the application of the use of the Virtual Chemistry Lab and evaluation of its implementation. The results obtained show that students' ability to apply software is quite good and their ability to acquire general scientific skills is around 80% and student responses are very positive at 89%.